An Update on the Potential Application of Herbal Medicine in Promoting Angiogenesis - Li, Jingjing; Li, Renkai; Wu, Xiaoping; Zheng, Chengwen; Shiu, Polly Ho-Ting; Rangsinth, Panthakarn; Lee, Simon Ming-Yuen; Leung, George Pak-Heng (Frontiers in Pharmacology, 2022)
Angiogenesis, the formation of new capillaries from pre-existing vascular networks, plays an important role in many physiological and pathological processes. The use of pro-angiogenic agents has been proposed as an attractive approach for promoting wound healing and treating vascular insufficiency-related problems, such as ischemic heart diseases and stroke, which are the leading causes of death worldwide. Traditional herbal medicine has a long history and is considered effective and safe, although there is still a need for more in-depth study and evidence-based confirmation from controlled and validated trials. A growing number of in vitro and in vivo studies have reported that herbal medicines and their bioactive ingredients exert pro-angiogenic activity. The most frequently studied pro-angiogenic phytochemicals include ginsenosides from Panax notoginseng; astragalosides and calycosin from Radix Astragali; salvianolic acid B from Salvia miltiorrhiza; paeoniflorin from Radix Paeoniae; ilexsaponin A1 from Ilex pubescens; ferulic acid from Angelica sinensis; and puerarin from Radix puerariae. This review summarises the progression of research about these phytochemicals, especially those related to their pro-angiogenic mechanisms and applications in ischemic diseases, tissue repairing and wound healing. In addition, an outline of their limitations and the challenges during drug development is also presented.